2015
DOI: 10.1080/14616696.2015.1007153
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Informal Care Gap

Abstract: This article investigates the relationship between the 'gender informal care gap' -the relative contributions of women to informal care for non-co-resident relatives and other members of social networks, compared to men -and public care policies, level of care needs, labour market position and gendered care attitudes. Since the literature suggests that none of these factors alone can explain the gender informal care gap, we develop a model based on fuzzy-set/qualitative comparative analysis in order to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Roit et al (2015) show that the largest gender-gap in care provision is found in the Mediterranean countries (Italy, followed by Spain and Greece), whereas the Nordic countries display the lowest gender-gap (Sweden, followed by Denmark 2 ). As Sainsbury (1999: 99) argues, the Scandinavian model undermines 'gender differences in entitlements and promotes equality between the sexes in social provision'.…”
Section: Welfare State and Social Supportmentioning
confidence: 95%
See 2 more Smart Citations
“…Roit et al (2015) show that the largest gender-gap in care provision is found in the Mediterranean countries (Italy, followed by Spain and Greece), whereas the Nordic countries display the lowest gender-gap (Sweden, followed by Denmark 2 ). As Sainsbury (1999: 99) argues, the Scandinavian model undermines 'gender differences in entitlements and promotes equality between the sexes in social provision'.…”
Section: Welfare State and Social Supportmentioning
confidence: 95%
“…Nevertheless, differences in the distribution of public and private sources of care provision are closely connected to the gender-gap in care provision (Roit et al, 2015), as several studies have shown that women have usually been the primary caregivers (Harris and Morgan, 1991;Kalmijn, 2007;Rosenthal, 1985;Van Gaalen and Dykstra, 2006). Therefore, given the differences in the gender-gap in care provision between Norway and Spain, we argue that the effect of gender on expectations of economic support should differ between the two countries.…”
Section: Hypothesesmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, gender issues related to care for older people have received significant attention in the literature and gender differences are particularly pronounced in filial care [15][16][17]. Gender inequalities are a salient issue in familialist regimes, as both legal obligations and public support for the caring role of the family encourage support in a gender-specific way (see [18]).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the impact of the type of LTC policy on caregiving in families are starting to emerge, with a specific focus on unfavorable consequences of cash for care schemes. One of them is increased gender inequality in intergenerational care (Da Roit, Hoogenboom, & Weicht, 2015;Pavolini & Ranci, 2008). Intended to enable choice in care receipt and to support the activities of informal carers, evidence suggests that cash for care benefits subtly incentivize women to fall back on traditional divisions of roles.…”
Section: Unfavorable Consequences Of Cash For Care Schemesmentioning
confidence: 99%